The politics and aesthetics of humour in an age of comic controversy. - Nieuwenhuis, Ivo; Zijp, Dick (European Journal of Cultural Studies, 2022)
In this introductory article to a special issue on 'the politics and aesthetics of humour', we argue that today in the Global North, humour forms a heavily debated topic, which is deeply embedded in political struggles over who are included and excluded in post-9/11 nation states. Under influence of the recent shift from post-politics to hyper-politics in the European and Anglo-American public sphere, we observe a repoliticisation of humour. To understand how humour in this cultural conjuncture is related to processes of power distribution and contestation, a cultural studies approach is needed. We outline the following four main characteristics of such an approach: (1) it studies humour in the plural, as a set of cultural and aesthetic conventions embodied in practices that are not guided by one grand social or political function, (2) it seeks to understand how humour is embedded in relationships of power, and contributes to the negotiation, contestation and maintaining of social hierarchies, (3) it looks specifically at the form and style of humour, its aesthetics and how on this formal level, political meaning is created and (4) it contends that, while humour often purposefully creates confusion and ambiguity, through its rhetorical and aesthetic operations it also has the ability to foreground particular interpretations, thus making the meaning of comic utterances less undecided than is often claimed.